Misregulation of Drosophila Sidestep Leads to Uncontrolled Wiring of the Adult Neuromuscular System and Severe Locomotion Defects - Kinold, Jaqueline C.; Brenner, Marcel; Aberle, Hermann (Frontiers in Neural Circuits, 2021)
Holometabolic organisms undergo extensive remodelling of their neuromuscular system during metamorphosis. Relatively little is known whether or not embryonic guidance molecules and axonal growth mechanisms are re-activated for the innervation of a very different set of adult muscles. Here, we show that the axonal attractant Sidestep (Side) is re-expressed during Drosophila metamorphosis and indispensable for neuromuscular wiring. Mutations in side cause severe innervation defects in all legs. Neuromuscular junctions (NMJs) show a reduced density or are completely absent at multi-fibre muscles. Misinnervation strongly impedes, but does not completely abolish motor behaviours, including walking, flying or grooming. Overexpression of Side in developing muscles induces similar innervation defects, e.g. at indirect flight muscles, which causes flightlessness. Since muscle-specific overexpression of Side is unlikely to affect central circuits, the resulting phenotypes seem to be a direct consequence of faulty muscle wiring. We further show that mutations in beaten path Ia (beat), a receptor for Side, results also in similar albeit weaker adult locomotion phenotypes, indicating that embryonic guidance pathways seem to be reactivated during metamorphosis.